PREVALENCE OF GINGIVAL HYPERPIGMENTATION AMONG OLDER INDIVIDUALS MORE THAN 40 YEARS OF AGE - T, Santhosh; G, Kaarthikeyan; malaiappan, Sankari (International Journal of Psychosocial Rehabilitation, 2019)
the basal and suprabasal cell layers of the epithelium. It can also be caused by some systemic disorders. Sometimes pigmentations are due to the skin tone of the particular individual. The prevalence of gingival hyperpigmentation among older individuals still remains an area of study where it should be fully investigated. The main purpose of this study is to evaluate the prevalence of gingival hyperpigmentation among individuals more than 40 years of age. Data retrieved from saveetha dental college. Diagnostic photographs both intra oral frontal and intra oral lateral photographs of 100 patients were retrieved and assessed with the help of SPSS software. The findings of this study shows that there is no age and gender correlation with pigmentation. Thus our study concludes that there is moderate to severe gingival pigmentation among older individuals and it has become one of the esthetic concerns among people. With the emergence of depigmentation treatment as one of the important aray of periodontal therapy.